2017
DOI: 10.1016/j.bpj.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

A Degraded Fragment of HIV-1 Gp120 in Rat Hepatocytes Forms Fibrils and Enhances HIV-1 Infection

Abstract: Identification of the host or viral factors that enhance HIV infection is critical for preventing sexual transmission of HIV. Amyloid fibrils derived from human semen, including semen-derived enhancer of virus infection and semenogelins, enhance HIV-1 infection dramatically in vitro. In this study, we reported that a short-degraded peptide fragment 1 (DPF1) derived from native HIV-1 envelope protein gp120-loaded rat hepatocytes, formed fibrils by self-assembly and thus enhanced HIV-1 infection by promoting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It has been reported that the addition of a small amount of preformed SEVI fibrils as seeds to a suspension of soluble PAP248–286 monomers promotes fibril polymerization and eliminates the lag phase for assembly [ 23 , 29 ]. In the present study, myricetin-mediated inhibition of SEVI aggregation seeded by preformed fibrils was determined by the ThT assay.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that the addition of a small amount of preformed SEVI fibrils as seeds to a suspension of soluble PAP248–286 monomers promotes fibril polymerization and eliminates the lag phase for assembly [ 23 , 29 ]. In the present study, myricetin-mediated inhibition of SEVI aggregation seeded by preformed fibrils was determined by the ThT assay.…”
Section: Resultsmentioning
confidence: 99%
“…PAP257–267 is considered to be the central region of PAP248–286, and this amyloidogenic region of the SEVI precursor peptide PAP248–286 has high fibril-forming propensity. Coincidentally, PAP268–271 has been reported to play an important role in promoting SEVI fibrillation [ 23 ]. Residues G260–N265 are thought to be involved in the initiation of fibrillation [ 40 ], and residues V262–H270 were shown to be the amyloidogenic region for SEVI fibrillation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations